PENDEKATAN FUZZY-QUALITY FUNCTION DEPLOYMENT DALAM PEMILIHAN SUPPLIER - Suhartini Suhartini (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
PT. Liku Telaga is one of the companies engaged in chemical industry production base with sulfuric acid and aluminum sulfate. To be able to produce a product according to customer’s spesification, PT. Liku Telaga wanted to make improvements in the process, especially in procurement division. Where it relates to the process of selecting suppliers for the supply of raw materials in the production process. Problems encountered in this study is to determine the supplier selection and allocation of orders in accordance with the company spesification. Fuzzy Method-Quality Function Deployment is used to measure supplier performance. The purpose of this research is to be able to meet optimal solutions in selecting suppliers accordance to company criteria. Score each supplier sulfur is PT. Ocean area (Singapore) with a score of 200.8, Standard Chemical Corp. Pte.Ltd (Singapore) with a score of 164.3, PT. Yosomulyo Jajag (Surabaya) with a score of 160.3 and CV. Archindo (Gresik) with a score of 152.0. Score of each supplier of aluminium hydroxide is Hindalco Industries Limited (India) with a score of 219.0, PT. Bisindo Kencana (Jakarta) with a score of 186.0, Sumitomo (Brazil) with a score of 165.9, and Chemindus SDN BHD (Malaysia) with a score of 135.8.